Growth Mindset and Cognitive Engagement of Female EFL Learners: Contribution of Risk-Taking as a Mediator - لیلا حسن زاده; سعیده آهنگری (Journal of Applied Linguistics)
Many difficulties learners experience during language learning interfere with their performance, and those associated with their psychology play an integral role in this process. Underpinned by Bandura’s social cognitive theory and Dweck’s implicit theory of intelligence, this article explored how language mindsets influenced female EFL learners’ cognitive engagement through the mediation of risk-taking. Following a quantitative design and drawing on stratified sampling, the researchers ran the Power Analysis Calculator and selected 384 language learners from six institutes of Tabriz, Iran. The data were collected by three questionnaires, including the Language Mindset Inventory of Lou and Noels (2017), University Student Engagement Inventory (USEI) designed by Maroco et al., (2016), and the Barratt Impulsiveness Scale (BIS) of Patton, Stanford and Barratt (1995). The PLS-SEM analysis showed that learners’ growth mindsets were directly related to cognitive engagement. Furthermore, risk-taking significantly mediated this relationship. This finding provides some implications for school psychology to develop in students self-theories that highlight growth and competence instead of limitation and inactivity.